2021
DOI: 10.1093/bib/bbab455
|View full text |Cite
|
Sign up to set email alerts
|

Integrative COVID-19 biological network inference with probabilistic core decomposition

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for millions of deaths around the world. To help contribute to the understanding of crucial knowledge and to further generate new hypotheses relevant to SARS-CoV-2 and human protein interactions, we make use of the information abundant Biomine probabilistic database and extend the experimentally identified SARS-CoV-2-human protein–protein interaction (PPI) network in silico. We generate an extended network by integrating informatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 88 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Genomic sequencing has shown that SARS-CoV-2 shares approximately 79% similarities with SARS-CoV and 50% similarities with MERS-CoV. Recent research indicates that the identifications of molecular mechanisms ( Zhang et al, 2021a ), cellular functions ( Alipoor et al, 2021 ), and biological network activities ( Habibi et al, 2021 ; Guo et al, 2022 ) are important to better understand the intricacies of disease biology and potentially lead to new therapies in treating COVID-19. The virus can invade cellular processes by moving proteins and genetic material from cells, resulting in the formation of new virus particles ( Cohen, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic sequencing has shown that SARS-CoV-2 shares approximately 79% similarities with SARS-CoV and 50% similarities with MERS-CoV. Recent research indicates that the identifications of molecular mechanisms ( Zhang et al, 2021a ), cellular functions ( Alipoor et al, 2021 ), and biological network activities ( Habibi et al, 2021 ; Guo et al, 2022 ) are important to better understand the intricacies of disease biology and potentially lead to new therapies in treating COVID-19. The virus can invade cellular processes by moving proteins and genetic material from cells, resulting in the formation of new virus particles ( Cohen, 2016 ).…”
Section: Introductionmentioning
confidence: 99%